Integrating The TPB With Economic Theories: The Case of Graduate Entrepreneur - Sulaiman, Sabirah; Lim, Hock Eam; Viswanathan, K. Kuperan (UUM Press, 2019)
The purpose of this article is to examine and integrate the theoretical approaches to the study of graduate entrepreneurship. The emphasis is on the use of economic theory to study the actual behaviour of entrepreneurship. The aim is to provide an overview of how the economic theories (utility maximisation theory and risk-taking behaviour theory) can be integrated with the theory of planned behaviour (TPB) to develop a theoretical framework to understand entrepreneurship behaviour.